2007
DOI: 10.1136/qshc.2006.019901
|View full text |Cite
|
Sign up to set email alerts
|

Rates and types of events reported to established incident reporting systems in two US hospitals

Abstract: Background: US hospitals have had voluntary incident reporting systems for many years, but the effectiveness of these systems is unknown. To facilitate substantial improvements in patient safety, the systems should capture incidents reflecting the spectrum of adverse events that are known to occur in hospitals. Objective: To characterise the incidents from established voluntary hospital reporting systems. Design: Observational study examining about 1000 reports of hospitalised patients at each of two hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
5
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 27 publications
3
69
5
6
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Many clinicians are also reluctant to disclose details of adverse events (see Box 1) to patients and their families. 11,12 Multiple factors are thought to contribute to this, including the psychological effects on clinicians of involvement in adverse patient safety events, a fear by them that their organisation will take a punitive approach to any investigation, and a lack of confi dence that systems will change as a result of reporting.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Many clinicians are also reluctant to disclose details of adverse events (see Box 1) to patients and their families. 11,12 Multiple factors are thought to contribute to this, including the psychological effects on clinicians of involvement in adverse patient safety events, a fear by them that their organisation will take a punitive approach to any investigation, and a lack of confi dence that systems will change as a result of reporting.…”
Section: Introductionmentioning
confidence: 99%
“…Number of studies showed a measurable percentage of adverse events reported with respect to the total admission taken place. 4,5 In our study, the patient/family dissatisfaction with care received, documented or expressed during the current admission was the most common incident reported. Hospital acquired infection/sepsis being the second most common incident reported in admitted patients.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to our study nurses, allied health professionals and doctors were the persons reporting any adverse event happening in a patient. 4,7,8,10,11 In our study adverse events presented with untoward outcome, with 34.8% causing admission in wards, 24.6% causing unexpected death, 28.6% causing disability at the time of discharge and 48.7% causing prolonged stay. Similarly in other studies untoward outcome presented as death or permanent loss of function, permanent lessening of function, additional surgery or increased length of stay.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A system that reviews adverse outcomes or near misses can identify latent factors before a major disaster takes place, but the system will enhance safety only if those with influence engage in it. 45 Important as engagement is, change is more likely to occur if those analyzing the near misses or adverse outcomes use the language of human factors to facilitate comprehension of the interaction between the practitioners and their environment.…”
Section: Managermentioning
confidence: 99%